Contribution of Cultural Intelligence to Job Performance of Domestic Hotel Employees in Thailand: The Mediating Roles of Communication Effectiveness and Job Stress - Ratasuk, Akaraphun (Thammasat Review, 2020)
This study investigated the contributions of cultural intelligence (CQ) on job performance. Communication effectiveness and job stress were proposed as two competencies that mediated the linkage between cultural intelligence and job performance. Survey data were collected from 427 frontline employees working for domestic chain hotels in Thailand. The results computed from a partial least squares (PLS) regression analysis showed that communication effectiveness and job stress mediated the linkage between cultural intelligence and job performance of the frontline hotel employees. The results also showed that communication effectiveness negatively and partially mediated the relationship between CQ and job stress, and job stress positively and partially mediated the relationship between communication effectiveness and job performance of the frontline hotel employees. The findings indicate that CQ can improve frontline hotel employees' job performance by increasing their communication effectiveness and reducing their job stress.